UF/IFAS Florida Trees Tutorial - Ryan W. Klein; Larsen McBride; Howard Beck (EDIS)
The UF/IFAS Florida Trees website contains a database of detailed information on over 1000 trees. The website's Tree Recommendation Tool presented in this publication can help the user do a thorough site analysis, identify important characteristics of that site, and then recommend trees for that site based on those characteristics. Likewise, the website's Tree Search and Identification tools can help a user search the database for trees matching characteristics that the user specifies. Overall, the information found on the website can assist both homeowners and professionals with addressing species selection issues that may impact tree survivability and long-term performance.